Vitamin D3 Adjuvant Treatment Stimulate Interleukin-10 Expression in Children with Nephrotic Syndrome Without Affecting to Clinical Outcome and Glucocorticoid Receptor Expression - Husnul Asariati; Krisni Subandiyah; Loeki Enggar Fitri (Journal of Tropical Life Science, 2014)
Idiopathic nephrotic syndrome (INS) is the most glomerular disease that occurred in childhood with high rate morbidity. Glucocorticoid is drug of choice for INS and responsiveness to this drug determined prognosis. Glucocorticoid upregulate transcription of anti-inflammatory cytokines such as IL-4 and IL-10. IL-10 is an anti-inflammatory cytokine and has multiple role in immune response include modulate Th1/Th2 response. Vitamin D3 interact with glucocorticoid signaling. Administered active form of vitamin D3 increase dexamethasone-induced IL-10 expression by regulatory T cells in steroid resistant asthmatic patient. Here we showed increase of CD4+IL10+ expression after treatment both prednisone only and combination prednison with vitamin D3. Both in new-onset NS or rare relaps NS, combination treatment prednisone + vitamin D3 increase CD4+IL10+ expression significantly compared to prednisone-only treated group (p= 0.003), which first group (new-onset nephrotic syndrome + prednisone and vitamin D3 treatment) showed the most CD4+IL10+ expression enhancement (9.53±3.89). However this study failed to show a correlation between CD4+IL-10+ expression after prednisone and vitamin D3 treatment with clinical outcome (linear regression test, p= 0,125). This study also showed that there was a no correlation between CD4+IL-10+ expression and CD3+GR expression after prednison + vitamin D3 treatment (p= 0.088). CD4+IL-10+expression in new-onset and rarely relapsing nephrotic syndrome patients higher in prednisone + vitamin D3 treated group than prednisone-only treated group. There is no correlation between CD4+IL-10+expression and CD3+GR expression nor CD4+IL-10+expression and clinical outcome.